How do hospital doctors manage patients with medically unexplained symptoms: a qualitative study of physicians. (February 2017) - Warner, Alex; Walters, Kate; Lamahewa, Kethakie; Buszewicz, Marta
Objective: Medically unexplained symptoms are a common presentation in medical practice and are associated with significant morbidity and high levels of service use. Most research exploring the attitudes and training of doctors in treating patients with unexplained symptoms has been conducted in primary care. This study aims to explore the ways in which doctors working in secondary care approach and manage patients with medically unexplained symptoms. Design: A qualitative study using in-depth interviews and thematic analysis. Setting: Three hospitals in the North Thames area. Participants: Twenty consultant and training-grade physicians working in cardiology, gastroenterology, rheumatology and neurology. Main outcome measure: Physicians' approach to patients with medically unexplained symptoms and their views on managing these patients. Results: There was considerable variation in how the physicians approached patients who presented with medically unexplained symptoms. Investigations were often ordered without a clear rationale and the explanations given to patients when results of investigations were normal were highly variable, both within and across specialties. The doctor's level of experience appeared to be a more important factor in their investigation and management strategies than their medical specialty. Physicians reported little or no formal training in how to manage such presentations, with no apparent consistency in how they had developed their approach. Doctors described learning from their own experience and from senior role models. Organisational barriers were identified to the effective management of these patients, particularly in terms of continuity of care. Conclusions: Given the importance of this topic, there is a need for serious consideration as to how the management of patients with medically unexplained symptoms is included in medical training and in the planning and delivery of services.